Comparison of liver injury and inflammatory response following conventional and drug-eluting bead transcatheter chemoembolization in hepatocellular carcinoma - Ran You; Bin Leng; Chendong Wang; Zeyu Yu; Lingfeng Diao; Ya Lu; Qingyu Xu; Guowen Yin (Discover Oncology)
Abstract Objective This study aimed to compare the extent of liver injury and the inflammatory response in patients with hepatocellular carcinoma (HCC) following conventional transarterial chemoembolization (cTACE) and drug-eluting bead transarterial chemoembolization (DEB-TACE). Methods Clinical data from October 2018 to October 2019 were prospectively collected to establish a database. The baseline clinical and demographic characteristics of patients in the two groups were matched using propensity score matching (PSM). Serum levels of hepatic function indicators and inflammatory cytokines were evaluated before treatment and five days post-treatment. Results A total of 134 participants were included in the analysis. Following 1:1 PSM, 43 patients remained in each group, with no significant differences observed in baseline characteristics. The median absolute concentration of aspartate aminotransferase (AST) was significantly lower in the DEB-TACE group five days after treatment. Among 18 patients who experienced idiosyncratic drug-induced liver injury, the DEB-TACE group exhibited a significantly lower proportion of cases. The alanine aminotransferase/alkaline phosphatase (ALT/ALP) ratio was notably higher in the cTACE group, while cholestatic-type liver injuries were predominant in the DEB-TACE group. Levels of MCP-1, IL-6, and IL-1β were lower in the DEB-TACE group five days post-treatment. Additionally, MCP-1 levels were significantly correlated with ALT levels and the type of liver injury. Similarly, IL-6 levels showed significant correlations with ALT, AST, and the type of liver injury. Conclusions DEB-TACE was associated with reduced acute liver injury, characterized primarily by cholestatic injury, and a milder inflammatory response compared to cTACE. Post-treatment levels of MCP-1 and IL-6 levels were correlated with aminotransferase levels and the type of liver injury. Trial registration: Chinese Clinical Trial Registry, ChiCTR-1800017781. Register URL link: https://www.chictr.org.cn/showproj.html?proj=30041 . Register date: 2018-8-14.